2020
DOI: 10.1002/14651858.cd012949.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for people with cystic fibrosis

Abstract: Analysis 1.4. Comparison 1 Probiotic versus placebo, Outcome 4 Faecal calprotectin (µg/g) -change from baseline -sensitivity analysis..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 64 publications
(16 reference statements)
0
22
0
Order By: Relevance
“…Regarding potential tools and methods for future therapeutics, probiotics could serve as a cost-effective approach for targeted manipulations, and there have already been several trials of probiotic usage in CF [13], some of which have incorporated Bifidobacterium species. However, none of these trials have investigated the impact of probiotics on bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding potential tools and methods for future therapeutics, probiotics could serve as a cost-effective approach for targeted manipulations, and there have already been several trials of probiotic usage in CF [13], some of which have incorporated Bifidobacterium species. However, none of these trials have investigated the impact of probiotics on bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…In that context, the efficacy of probiotics for improving health outcomes in children and adults with CF has been a much-debated issue [ 101 ]. A recent meta-analysis confirmed that probiotics significantly reduce fecal CLP in children and adults with CF; however, probiotics may make little or no difference to pulmonary exacerbation rates.…”
Section: Clp In Cystic Fibrosis and Non-cystic Fibrosis Bronchiectmentioning
confidence: 99%
“…A recent meta-analysis confirmed that probiotics significantly reduce fecal CLP in children and adults with CF; however, probiotics may make little or no difference to pulmonary exacerbation rates. Nevertheless, further evidence is required before firm conclusions can be made [ 101 ].…”
Section: Clp In Cystic Fibrosis and Non-cystic Fibrosis Bronchiectmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Cochrane review included 12 randomised controlled trials that looked at probiotics for CF but none of the trials reported on GI symptoms. 13 Early work using MRI is aiming to identify physiological markers of where the CF GI system differs from that of healthy controls. 14 New treatments that correct the underlying defect in CF transmembrane conductance regulator (CFTR) proteins have been shown to be effective in pwCF who have specific gene mutations.…”
Section: Open Accessmentioning
confidence: 99%